Sustainable Development, Circular Economy and Popular Practices: Does the Relationship between Society and the Environment Need the Economy? - Blot, Denis (Acciones e Investigaciones Sociales, 2022)
The circular economy broadens and clarifies sustainable development by offering it a formal framework of concrete projects. This article shows that these notions of sustainable development and circular economy are based on the widely shared assumption of the existence of an economic sphere that obeys its own rules. It questions the consequences that such a belief has on the non-commercial economic practices contained in popular social frameworks based on inter-knowledge, resistance to market logic and community solidarity. The circular economy camouflages the ecological nature of these practices and sometimes even makes them disappear. Such a diminution in importance of ecology with respect to the economy obscures the social consequences of developing the circular economy while reinforcing control of the economy over its social components. The article defends the hypothesis that the circular economy, which is the seed of sustainable development, is a social project that is built without society’s intervention.
Keywords: Circular economy, sustainable development, society, environment.